Cinnamon- An Immune modulator food additive to coronavirus - Ravindra Verma; Prakash S. Bisen (Journal of Food Bioactives, 2022)
This study explores the potential role of cinnamaldehyde from cinnamon to elicit immunity against the pathogens of COVID-19. In the culture of traditional and herbal treatments, it was more valuable than gold. It has been observed that coronavirus infects cells of an organism including innate and adaptive immune cells. Cinnamaldehyde, eugenol, and other secondary metabolism of cinnamon extract, have a potential role to interact with spike protein of coronavirus. Available literature supports the suitability of cinnamon for acute respiratory infectious disease syndromes. It might be a promising source for the immune system to control viral infections like COVID-19. Preclinical and clinical trials are necessary for the safety and efficacy of the drug.